The Effects of Perceived Ease of Use and Security on User Satisfaction and Loyalty of DANA E-Wallet Users in Pontianak City - Nur Syaripah Aini; Neni Triana M (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of Perceived Ease of Use and Security on User Satisfaction and User Loyalty among DANA e-wallet users in Pontianak City. The research employs a quantitative associative approach using primary data collected from 100 respondents selected through purposive sampling and proportionally distributed across six districts. The instrument was measured using a five-point Likert scale, while data analysis was conducted using SEM-PLS with SmartPLS software. The evaluation of the measurement model indicates that all constructs meet the criteria for validity and reliability (with CR and AVE values exceeding the minimum thresholds). In the structural model, Security is proven to have a positive and significant effect on both satisfaction and loyalty, and satisfaction also has a significant effect on loyalty. In contrast, Perceived Ease of Use does not have a significant effect on satisfaction but is found to have a negative and significant effect on loyalty. This finding constitutes the main scientific contribution of the study, as it demonstrates that within a highly competitive e-wallet market, ease of use may function as a hygiene factor—being easy to use does not automatically foster loyalty and may even encourage switching behavior when users are more sensitive to promotions, features, or other perceived benefits. The mediation analysis shows that satisfaction mediates the effect of Security on loyalty but does not mediate the relationship between Perceived Ease of Use and loyalty. From a practical perspective, DANA should prioritize strengthening security, privacy protection, and fraud prevention as the foundation for building long-term satisfaction and loyalty, while selectively enhancing the user experience in core transaction processes. Future research is recommended to incorporate variables such as trust, perceived value, service quality, and switching intention to better explain the mechanisms underlying loyalty formation in digital payment services.